2023
DOI: 10.1111/jcmm.17918
|View full text |Cite
|
Sign up to set email alerts
|

OPA1, a molecular regulator of dilated cardiomyopathy

Jiaqi Chen,
Jianan Shao,
Yaoyao Wang
et al.

Abstract: Dilated cardiomyopathy (DCM) is a disease with no specific treatment, poor prognosis and high mortality. During DCM development, there is apoptosis, mitochondrial dynamics imbalance and changes in cristae structure. Optic atrophy 1 (OPA1) appears at high frequency in these three aspects. DCM LMNA (LaminA/C) gene mutation can activate TP53, and the study of P53 shows that P53 affects OPA1 through Bak/Bax and OMA1 (a metalloprotease). OPA1 can be considered the missing link between DCMp53 and DCM apoptosis, mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Previous studies have identified that DRP1 is the mitochondrial fission core component, which is gathered into circular structure to mediate mitochondrial fission by mitochondrial cleavage alongside mitochondrial tubules [ 36 ]. OPA1 maintains fused mitochondrial network, and drives inner membrane fusion at the mitochondrial inner membrane [ 37 ]. These findings revealed that high glucose reduced membrane potential of mitochondria, suppressed ATP production, enhanced DRP1 but decreased OPA1 expression and up-regulated intracellular ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that DRP1 is the mitochondrial fission core component, which is gathered into circular structure to mediate mitochondrial fission by mitochondrial cleavage alongside mitochondrial tubules [ 36 ]. OPA1 maintains fused mitochondrial network, and drives inner membrane fusion at the mitochondrial inner membrane [ 37 ]. These findings revealed that high glucose reduced membrane potential of mitochondria, suppressed ATP production, enhanced DRP1 but decreased OPA1 expression and up-regulated intracellular ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…OPA1 is a mitochondrial guanosine triphosphatase (GTPase) that is widely distributed in the inner membrane of mitochondrial cristae. Its physiological and functional roles include regulating mitochondrial fusion, controlling mitochondrial cristae structure, maintaining mitochondrial integrity, and inhibiting apoptosis-related cytochrome c release [24]. Mitochondrial disruption, respiratory complex I inactivation, and reduced ATP production have been observed in neural cells derived from OPA1mutated induced pluripotent stem cells [25].…”
Section: Introductionmentioning
confidence: 99%